Research on Social Media Tourism Marketing in the Post-epidemic Period - Xie Xiaoluan (Universitas Muhammdiyah Yogyakarta, 2021)
Since 2020, the outbreak of covid-19 has changed the operation mode of many industries, and also has a great impact on the global tourism industry. At the same time, it also promotes the transformation of the tourism industry, which is more dependent on the real economy, to the Internet economy. The use of social media for tourism marketing is a hot spot in recent years, and the outbreak of the epidemic has intensified the development of this model. This paper analyzes the characteristics of social media to explain why it is more suitable for tourism marketing than traditional media, and summarizes the tourism marketing strategies and means of social media. Social media has rich forms of expression, such as text, pictures, audio, video, live broadcast, etc., which can be selected according to the nature of tourism destination. Through the use of precision marketing, word-of-mouth marketing, celebrity effect and other marketing strategies, it can also improve the audience's willingness to travel during the post epidemic period, and promote the recovery and development of tourism.